Financial Feasibility Of Shrimp Paste Kecepai (Acetes Indicus) Production In Pangkalan Susu, Langkat Regency - Jerri Simarsoit; Eni Yulinda; Lamun Bathara (Journal of Food System & Agribusiness, 2021)
The objective of this research is to calculate the amount of investment to establish shrimp paste business in Pulau Kampai Village and to evaluate the level of feasibility of the Kecapai shrimp paste (Acetes indicus) processing business based on financial aspects (financial) using undiscounted and discounted investment criteria analysis and sensitivity. The survey method was employed in this research, and the respondents were determined through census. The data was taken directly from the 32 shrimp paste entrepreneurs using observation, interviews, and documentation. As per the results of this study, the investment needed to initiate a shrimp paste business in the micro scale is Rp8.089.018,- while a resource needed in the small scale is Rp12.425.200,-. when it is not shrimp season or season in a month, micro and small scale businesses are considered eligible to continue because they exceed the break even point, and the results of the undiscounted investment analysis BEP volume and price of production when it is not season or season in a month micro and small scale are declared eligible to continue because they exceed the break even point. Nevertheless, the ROI for micro and small scale when it is not season and season is declared unfeasible because it will be less than one. The NPV, IRR, B/C Ratio, PP, micro, and small scale are declared viable to produce for the computation of the discounted investment criteria since they match the eligibility criteria. Nevertheless, a sensitivity analysis reveals that one possibility, namely a fall in selling prices and a rise in variable expenses, renders the business unviable.